STUDY TENTANG PEMUNGUTAN ZAKAT PENGHASILAN PEGAWAI PADA UNIT PENGUMPUL ZAKAT KANTOR KEMENTERIAN AGAMA KOTA SALATIGA - Ahmad Mustahal; Abdullah Kelib (UNISSULA Semarang, 2017)
Islam gives references, beliefs, and ways of life so that human beings are able to overcome the problems in the world, and reach to everlasting happiness in the afterlife. Zakat is one aspect of Islamic teachings that potential to be an instrument of empowerment of the ummah and poverty alleviation, and become a symbol of harmonious relationships among human beings. The Birth of Act Number 23 Year 2011 on the Management of Zakat marks a new era of national zakat transformation that has spawned a new paradigm of zakat management in the country. Which BAZNAS acts as a regulator of zakat management nationally, is expected to perform its duties and functions in an accountable and professional. Here UPZ has a very important role for BAZNAS. Similarly UPZ Office Ministry of Religious Affairs SalatigaIt is interesting to discuss how the implementation of Act Number 23 of 201 on Zakat Management, what constraints arise in the management of the collection of zakat on UPZ Office of Religious Affairs Ministry of Salatiga City, and how the solution to the barriers of management of zakat collection at UPZ Office Ministry of Religious Affairs Salatiga .Implementation of Law Number 23 Year 2011 on Zakat Management requires the integration and synergy of all lines of government, scholars, community leaders and zakat managers, socialization and training of professional zakat management and optimization of BAZNAS role in UPZ empowerment. BAZNAS is expected to be more optimal in carrying out its duties and functions, and increase accountability and professionalism to increase public confidence.Keywords: Zakah on Employee Income, Collectors of Zakah